In recent years, export of ornamental fish from Indonesia increased for every year in quantity and value. There are thirty eight companies with the ornamental fish export business. In this global competition era, the product quality stimulates company's competitiveness. This research has aim to see how far the TOM concept has been applied to improve the business performance of CV Banyu Biru. CV Banyu Biru hold a customer's satisfaction strategy for competing with competitors. The strat - Iis Diatin; Narni Farmayanti; Syanni Dian Nita (Buletin Ekonomi Perikanan, 2006)
In recent years, export of ornamental fish from Indonesia increased for every year in quantity and value. There are thirty eight companies with the ornamental fish export business. In this global competition era, the product quality stimulates company's competitiveness. This research has aim to see how far the TOM concept has been applied to improve the business performance of CV Banyu Biru. CV Banyu Biru hold a customer's satisfaction strategy for competing with competitors. The strategy is to fill up the customer's demand and satisfaction by serving and keeping product quality. We can see the problems of TOM and how far the TOM have been applied in this company by observing the company's quality management in relation with the indicators, principles, and the basic elements of TOM. In identifying the existing problem, the research use the Analytical Hierarchy Process (AHP) method by making hierarchy. The results of this research shows that there are five main problems. That the company always put in priority. These problems are product quality, product delivery timing, production continuity, product amount and production costs. The alternative for improvement are teamwork, training, benchmarking, information system, technology, product variation, and also the improvement in management info administration system. The priority of joined management perception to elements of TOM are company vision and mission, standardization, internal auditing, organization, facilities, human resources and training.